2021
DOI: 10.1177/00034894211033366
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Vocal Cord Motion Among Pediatric Patients

Abstract: Objectives: Patients with vocal cord paralysis can experience feeding, respiratory, and vocal problems leading to disability and decreased quality of life. Current evidence suggests waiting a period of 12 months for spontaneous recovery before permanent interventions. This study aims to determine the time to recover spontaneously and vocal cord movement in a pediatric population and create a model for evidence-based patient counseling. Study Design: Retrospective longitudinal cohort study. Methods: The report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A recent study linked gastrointestinal comorbidities to delayed recovery and no recovery of vocal fold motion compared to patients without gastrointestinal comorbidities. 22 Another consideration in this cohort is the overall inpatient mortality rate of 2.9%. Due to the data reporting restraints of PHIS, no conclusion can be made whether mortality is directly a result of BVFD, the associated complex condition, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study linked gastrointestinal comorbidities to delayed recovery and no recovery of vocal fold motion compared to patients without gastrointestinal comorbidities. 22 Another consideration in this cohort is the overall inpatient mortality rate of 2.9%. Due to the data reporting restraints of PHIS, no conclusion can be made whether mortality is directly a result of BVFD, the associated complex condition, or both.…”
Section: Discussionmentioning
confidence: 99%
“…The importance between feeding and vocal fold paralysis is well‐established, however, the specific relationship between gastrointestinal comorbidities and BVFD is limited. A recent study linked gastrointestinal comorbidities to delayed recovery and no recovery of vocal fold motion compared to patients without gastrointestinal comorbidities 22 …”
Section: Discussionmentioning
confidence: 99%
“…4 pUVFP due to cardiac surgery or those with dysphonia alone are less likely to recover, whereas congenital cases and those associated with aspiration are more likely to recover. 4 Prestwood et al reported that among 36 patients who recovered spontaneously, 80.6% had early recovery (within 12 months) and 19.4% had late recovery. Within the early recovery group, most recovered within 9 months, with only a 3% chance of recovery between 9 and 12 months.…”
Section: Natural History Of Pediatric Uvfpmentioning
confidence: 99%
“…The recommendations for the management of pUVFP are predominantly based on Level 4 evidence. [2][3][4][5] One systematic review and meta-analysis with Level 2 evidence are presented. 1…”
Section: Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation